Engineering vulnerability evaluation of building structures in coastal areas considering the effects of corrosion - Chi, Xiaona; Xu, Anna; Liu, Yajie; Lun, Peiyuan (Frontiers in Materials, 2023)
Chloride-induced corrosion is an important factor that affects the durability of building structures in coastal areas; it causes serious deterioration of reinforced concrete (RC) structures and leads to structural failure. However, chloride-induced corrosion is a slow process which spans the whole service life of building structures, and many factors can affect their service life, such as location, structural design, and drug management. This paper aims to predict the service life of building structures in terms of chloride-induced corrosion and through the concept of engineering vulnerability. It first investigates the model of corrosion initiation of reinforcement, along with the consequent concrete cover cracking. Second, according to the characteristics of building structure and corrosion, it determines an evaluation index system of engineering vulnerability and establishes an evaluation method of engineering vulnerability, considering that corrosion is based on the AHP method and fuzzy comprehensive evaluation. Finally, using a case study of a pharmaceutical factory structure in a coastal city, this study verifies the feasibility of the assessment method considering corrosion effects.